A Bibliometric Analysis of Research on Selenium in Drinking Water During the 1990–2021 Period: Treatment Options for Selenium Removal - Abejon-Elias, R (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
A bibliometric analysis based on the Scopus database was carried out to summarize the global research related to selenium in drinking water from 1990 to 2021 and identify the quantitative characteristics of the research in this period. The results from the analysis revealed that the number of accumulated publications followed a quadratic growth, which confirmed the relevance this research topic is gaining during the last years. High research efforts have been invested to define safe selenium content in drinking water, since the insufficient or excessive intake of selenium and the corresponding effects on human health are only separated by a narrow margin. Some important research features of the four main technologies most frequently used to remove selenium from drinking water (coagulation, flocculation and precipitation followed by filtration; adsorption and ion exchange; membrane-based processes and biological treatments) were compiled in this work. Although the search of technological options to remove selenium from drinking water is less intensive than the search of solutions to reduce and eliminate the presence of other pollutants, adsorption was the alternative that has received the most attention according to the research trends during the studied period, followed by membrane technologies, while biological methods require further research efforts to promote their implementation. © 2022 by the author. Licensee MDPI, Basel, Switzerland.
Keywords: selenium; drinking water; treatments; bibliometric analysis; research trends